Rights and Reason : an Introduction to the Philosophy of Rights. - Gorman, Jonathan (Taylor and Francis, 2014)
In ""Rights and Reason"", Jonathan Gorman sets discussion of the 'rights debate' within a wide-ranging philosophical and historical framework. Drawing on positions in epistemology, metaphysics and the theory of human nature as well as on the ideas of canonical thinkers, Gorman provides an introduction to the philosophy of rights that is firmly grounded in the history of philosophy as well as the concerns of contemporary political and legal philosophy. The book gives readers a clear sense that, just as there are arguments about the content of rights, and just as there are myriad claims to right.